Phototherapy in treatment of rare dermatoses - Marianna B. Zhilova (Vestnik Dermatologii i Venerologii)
The review presents current data on the mechanisms of action of phototherapy methods in dermatology (UVB-311 therapy, PUVA-therapy, UVA-1 therapy). They are realized in providing antiproliferative, immunomodulatory, antifibrotic, antipruritic, antimicrobial effects on pathological processes in the skin. The similarities and differences of the effects on cellular structures of different spectral ranges are described. The literature data on the effectiveness of phototherapy methods in rare nosological forms of skin diseases, including dermatoses with keratinization disorders, connective tissue diseases, vascular malformations, erythematous conditions based on a variety of therapeutic mechanisms are presented.